Senam Kreasi AHARIA untuk Menstimulasi Keterampilan Gerak Dasar Anak Usia Dini - Divanca, Jessica; Nurani, Yuliani; Hikmah, Hikmah (Indonesian Journal Publisher, 2024)
: The aim of this research is to develop creative gymnastics to stimulate basic motor skills in early childhood, especially in the age range of 5-6 years. This research employs the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The study uses a questionnaire as an instrument for expert reviews and an evaluation instrument for users, specifically 5-6-year-old children. The results of product validity testing by two content experts yielded a final score of 95%. The product's validity testing by gymnastics experts resulted in a final score of 82%. The effectiveness test on 5-6-year-old children produced a score of 87%. The research results indicate that creative gymnastics meet the criteria. Creative gymnastics as a physical activity can practically be used as a gross motor learning activity for teachers due to its variability.